Educational Brochures on Zoonotic and Infectious Diseases from Wildlife - Colgan, Michelle (My University, 2018)
Abstract The general public comes into contact with zoonotic threats every day, but do those people know of the possible diseases they could become infected with? People do not understand the severity of these diseases or the prevalence in any given backyard in the United States. Rabies, leptospirosis, tularemia, and the raccoon roundworm are a few of the zoonotic diseases that are commonly found in the wild. Education of the public is key to a healthy community that knows the correct response when coming into contact with wildlife. Prairie Park Nature Center in Lawrence, Kansas is the wildlife drop off for northeast Kansas. Every day they assess cases of wildlife that have been in the hands of the general public. The nature center also educates the community by teaching them about wildlife in their environment. The nature center consists of 100-acre nature preserve that incorporates wetlands, woodlands, and prairie habitats with a five acre lake. During the school year classes go to the nature center to get an up close view on eagles, owls, ferrets, and cockroaches, to name a few. If a wildlife animal is seen hurt by the general public, the nature center is contacted by the police department to determine how to handle the situation. A concern of the nature center was the lack of knowledge the police department has when it comes to rabies. This was addressed by organizing a presentation with a power point on rabies with the Lawrence Police Department. When the public drops off a wildlife animal, there needs to be a better way to communicate the potential dangers of zoonotic or infectious diseases the public has come into contact with by handling the animal. This was done by creating informational brochures that are easy for the public to comprehend that provide information of what to be aware of when coming into contact with certain wildlife. Since rabies is by far the most fatal disease, there was a brochure made for rabies separately. Other informational brochures that were made came from the most seen animals at the nature center which included infectious and zoonotic diseases from raccoons, opossums, squirrels, skunks, and bats.
Keywords: infectious; zoonotic; wildlife; public health; rabies; nature center